Bringing Religious Moderation Insights to “TikTok Da’wah” - Ahmad, Fairuz Zakiyah; Emeraldien, Fikry Zahria; Permatasari, Rahayu Dia; Zahda, Vizya Hanna (Jurnal Komunikasi Islam, 2022)
Preventing the spread of religious radicalism has remained popular issue in Indonesian nowadays. This is because Indonesia has long been vulnerable to Islamic radicalism ideologies. Many studies have revealed that young people have become the main target of the spread of Islamic extremist movement. This paper offers a textual analysis of ‘TikTok da’wah’ utilised by Muslim preachers to convey religious moderation teachings for young generation. In other words, it examines the use of Tiktok social media as a forum for mediating da'wah messages regarding religious moderation. The study results indicate that TikTok is an essential communication media for mubaligh to carry out da'wah for the millennial generation. In the hands of Islamic preachers, TikTok is likely to become a medium to build religious moderation insights amongs Indonesian youth.